Activation of LXR signaling ameliorates apoptosis of alveolar epithelial cells in Bronchopulmonary dysplasia - Yizhe Ma; Yameng Wang; Anni Xie; Luchun Wang; Yuqiong Zhang; Mingyan Tao; Xianhui Deng; Zhidan Bao; Renqiang Yu (Respiratory Research)
Abstract Background and purposes Liver X receptors (LXRs) are specialized nuclear receptors essential for maintaining cholesterol homeostasis, modulating LXR activity could have therapeutic potential in lung diseases. Bronchopulmonary dysplasia (BPD) is a chronic lung disease characterized by impaired alveolar development, in which apoptosis of alveolar epithelial cells is a key contributing factor. The current research focuses on exploring the potential mechanism by which the LXR pathway regulating alveolar epithelial type II cell apoptosis in response to hyperoxia exposure. Methods BPD infants and non-BPD preterm infants were enrolled to measure serum total cholesterol (TC) levels. To further investigate the role of cholesterol metabolism in BPD, a neonatal rat model of BPD was established, and in vitro studies were conducted using mouse lung epithelial cells (MLE12). These experiments aimed to explore the impact of hyperoxia on cholesterol metabolism and assess the effects of LXR agonist intervention. Results Elevated serum TC levels in BPD infants were observed, accompanied by lung cholesterol overload in BPD rats. Hyperoxia exposure also led to intracellular cholesterol accumulation in MLE12 cells, which may be attributed to the downregulated LXR signaling pathway. Activation of the LXR pathway prevented apoptosis and mitochondrial dysfunction in MLE12 cell. In BPD rats, intervention with the LXR agonist restored alveolar architecture and reduced alveolar epithelial type II cell apoptosis, which was associated with decreased oxidative stress and lung cholesterol accumulation. Conclusions Disrupted cholesterol metabolism and impaired homeostasis in premature infants may contribute to the development of BPD. Targeting LXR signaling may provide potential therapeutic targets in BPD. Clinical trial number Not applicable.